Cyclin D1 expression in penile cancer - Everton Duarte, Wesliany; Diniz Pinho, Jaqueline; da Costa Melo, Syomara Pereira; Rodrigo Diniz Duarte, Denner; da Guia Ribeiro do Carmo, Juliana Martins; Salim Khayat, André; Ribamar Rodrigues Calixto, José; Adriano Garcia Campos, Marcos [UNESP]; da Graça Carvalhal Frazão Correa, Rita; Machado Alencar Júnior, Antonio; Augusto Lima Teixeira-Júnior, Antônio; Eanes Barros Silva, Gyl (Impact Journals, 2024)
The main goal of the present study was to analyze the expression profile of cyclin D1 in patients with PC, and to determine possible correlations with clinical and histopathological features. A survey was conducted with 100 patients diagnosed with PC, who were treated at two reference hospitals in São Luís, Maranhão, Brazil, between 2013 and 2017. A review of clinical, epidemiological, and histopathological data was performed, Human Papillomavírus (HPV) DNA was detected using polymerase chain reaction (PCR) and cyclin D1 expression analysis was performed using immunohistochemical techniques. The data revealed that the absence of cyclin D1 expression was significantly associated with HPV-positive histological subtypes (p = 0.001), while its expression was associated with high-grade tumors (p = 0.014), histological subtype (p = 0.001), presence of sarcomatoid transformation (p = 0.04), and perineural invasion (p = 0.023). Patients with cyclin D1 expression exhibited lower disease-free survival compared to the cyclin D1-negative group, although the difference was not statistically significant. The results suggest that cyclin D1 may be a potential biomarker for PC, especially for poorer prognosis.
Keywords: biomarkers; cyclin D1; immunohistochemistry; penile neoplasms